Assessment of vulnerable and unstable carotid atherosclerotic plaques on endarterectomy specimens - BUTCOVAN, DOINA (Exp Ther Med, 2016)
The types of lesion instability responsible for the majority of acute coronary events frequently include plaque disruption and plaque erosion with superimposed thrombosis. The term ‘vulnerable plaque is used to describe atherosclerotic (ATS) plaques that are particularly prone to rupture and susceptible to thrombus formation, such as the thin-cap fibroatheroma (TCFA). The aim of the present study was to assess the morphological and histological differences between plaques that are unstable and those that are vulnerable to instability. Carotid artery endarterectomy specimens were obtained from 26 patients with carotid artery stenosis, consisting of 20 men and 6 women (age range, 35–80 years). Histological and morphometric methods were used to visualize and characterize the ATS plaques. Among the 26 carotid ATS plaques, 23% were stable, 23% were unstable and 54% were vulnerable. With regard to morphometric characteristics, the following mean values were obtained for the TCFA and unstable plaques, respectively: Fibrous cap thickness, 21.91 and 11.66 µM; proportion of necrotic core area in the total plaque area, 25.90 and 22.03%; and the proportion of inflammatory area in the total plaque area, 8.41 and 3.04%. No plaque calcification was observed in any of them. Since ATS coronary artery disease is considerably widespread and fatal, it is crucial to further study ATS lesions to obtain an improved understanding of the nature of vulnerable and unstable plaques. The methods used to detect plaque size, necrotic core area and fibrous cap thickness are considered to be particularly useful for identifying vulnerable and unstable plaques.